Analisis Kisah Lukman Al-Hakim dalam Al-Qur’an: Teladan dalam Pendidikan Karakter Generasi Z di Era Digital - Haris Adnan Alwi; Doni Pradana; Muhammad Syaifullah; Nabilla Nabilla (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
The rise of digital technology has brought about many benefits. Digitalization brings lots of changes in both positive and negative impacts on the character development of Generation Z. Therefore, preventive efforts are needed to overcome the moral decadence of the young muslim generation. This study aims to analyze the story of Lukman al-Hakim in educating children which has been narrated in the Qur'an. This study uses the library research method to analyze sources from books, tafsir books, and journal articles about Lukman al-Hakim’s story. Using content analysis techniques, this study concluded that moral education contained in the story of Lukman al-Hakim, which includes monotheism, worship, and morals, is material that is very much needed in the digital era. In the era of information technology, the role of parents as role models in children's character education is very much needed. Parents can guide their children to face the negative influence of digital media with a stronger religious character, including spiritual and moral values, worship to God, and fellowship to human beings. So that social media, which is often consumed by young generation in excess, is not used as a living guide in daily life.